Development of surface coating for underwater concrete structures - Sharmila, S; Keerthana, P (International Journal of Engineering and Technology, 2018)
Surface coating is the most focused research problem in the construction sites to repair the deteriorated concrete. Surface coating is an most necessary process to be performed in concrete to avoid the issues such as aesthetics, sealing, chemical resistance or abrasion resistance. These coatings are termed as special resins with proper compositions of materials which can prevent the transmission of water and contaminants while at the same time keeping the structure safe. This research work focuses on preparation of surface and the protective surface coating to protect the concrete. High performance coal tar with polyurethane coating materials are used to protect concrete from chemical and mechanical attack in interior, exterior and marine environments. Coal tar with polyurethane coating systems consist of two or more components blended and applied as a film, reacted chemically to form a protective film of high integrity, excellent adhesion, toughness and impact resistance. The coating were applied on 4”x4”x4” concrete cubes and kept for one week curing the samples, thickness of the coating were 70±5μm measured using hegman gauge. The tests such as Abrasion resistance, pull off test, water absorption test, chloride resistance test and Rapid chloride penetration test were performed and the results exemplifies that coal tar mixed with polyurethane coating can be used for underwater concrete structures.